Flowering tales : women exorcising history in Heian Japan. - Watanabe, Takeshi (Brill Academic Publishers : Brill, 2021)
"Telling stories: that sounds innocuous enough, but for the first chronicle in the Japanese vernacular, A Tale of Flowering Fortunes (Eiga monogatari), the health of its eleventh-century community was at stake. Flowering Tales is the first extensive literary study of this historical tale that covers about a hundred-fifty years of births, deaths, and happenings of late Heian society, a golden age of court literature. Takeshi Watanabe contends that the blossoming of tale literature, marked by The Tale of Genji, inspired what he describes as Eiga's affective history: an exorcism of embittered spirits whose stories needed to be retold to ensure peace. Tracing narrative arcs of political marginalized personages, Watanabe shows how Eiga, adapting the discourse and strategies of The Tale of Genji, reconnected wayward ghosts into the community through figural genealogies that relied not on blood, but on literary resonances. These reverberations, highlighted through comparisons to contemporaneous accounts in courtiers' journals, echo through shared details in funerary practices, lack of political support, and characterization. Flowering Tales reanimates these voices to trouble conceptions of history: how it ought to be recounted, who got to record it, and why remembering mattered"--